56.5k views
4 votes
What is the solution to the system of equations?

y = –3x – 2

5x + 2y = 15

User Orbatschow
by
5.1k points

1 Answer

4 votes

Answer:

x = -19

y = 55

Explanation:

Given:

y = –3x – 2 (rearrange)

3x + y = -2 -----> eq1

5x + 2y = 15 -----> eq2

multiply eq1 by 2:

6x + 2y = -4 -------> eq 3

By elimination: subtract eq2 from eq 3

( 6x + 2y) - (5x+2y) = -4 - 15

x = -19 (Answer)

substitute x = -19 into eq1

3(-19) + y = -2

-57 + y = -2

y = -2 + 57 = 55 (Answer)

User Nexonus
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.